2013
DOI: 10.1002/biot.201200205
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell durotaxis depends on substrate stiffness gradient strength

Abstract: Mesenchymal stem cells (MSCs) respond to niche elasticity, which varies between and within tissues. Stiffness gradients result from pathological conditions but also occur through normal variation, e.g. muscle. MSCs undergo directed migration even in response to shallow stiffness gradients before differentiating. More refined gradients of both stiffness range and strength are needed to better understand mechanical regulation of migration in normal and disease pathologies. We describe polyacrylamide stiffness gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
217
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(231 citation statements)
references
References 56 publications
(97 reference statements)
14
217
0
Order By: Relevance
“…Previous methods of reproducing in vivo stiffness gradients in culture systems are either complex (19,30,34,36,37) or lack the stiffness or gradient range (9,30,32) to interrogate the physiological mechanical landscape fully (Table S1). Therefore, we developed a method to fabricate planar PA hydrogels with linear stiffness gradients capable of spanning both biologically relevant ranges and disease conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous methods of reproducing in vivo stiffness gradients in culture systems are either complex (19,30,34,36,37) or lack the stiffness or gradient range (9,30,32) to interrogate the physiological mechanical landscape fully (Table S1). Therefore, we developed a method to fabricate planar PA hydrogels with linear stiffness gradients capable of spanning both biologically relevant ranges and disease conditions.…”
Section: Resultsmentioning
confidence: 99%
“…When mimicking the stiffness of neural (∼1 kPa), muscle (∼12 kPa), and bone (∼30 kPa) tissues (15,16), substrate stiffness can induce differentiation toward those specific tissue types. Furthermore, stem cells will migrate toward regions of higher stiffness in a process known as "durotaxis" (17)(18)(19), whereas neurons have shown preference for softer regions (20,21). Additionally, some cancer cell lines are inversely sensitive to substrate stiffness and thus show markedly different migration phenotypes (22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that mechanical cues, such as substrate stiffness or local stresses, have bearing on cellular behavior in many contexts [1][2][3][4][5][6]. For example, it has been shown that extracellular matrix (ECM) stiffness can promote the onset and progression of cancer [7][8][9][10], and that metastatic cancer cells exert greater traction forces than their healthy counterparts [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stiffness gradients have also been achieved using specially designed photomasks to control spatially the light exposure experienced by UV-crosslinked materials. This approach has been used to reconstitute natural stiffness variations present in normal or infarcted myocardial tissue, and to investigate mesenchymal stem cell durotaxis in culture (Tse and Engler, 2011;Vincent et al, 2013).…”
Section: D Spatial and Temporal Patterning Of Mechanicsmentioning
confidence: 99%